The casualty gap the causes and consequences of American wartime inequalities - Kriner, Douglas L.; Shen, Francis X. (New York ; Oxford : Oxford University Press, 2010)
Many have long suspected that when America takes up arms it is a rich man's war, but a poor man's fight. In 'The Casualty Gap' Douglas Kriner and Francis Shen renew the debate over unequal sacrifice by bringing to light mountains of new evidence on the inequality dimensions of American wartime casualties.
Description based on print version record.
Includes bibliographical references and index.
Keywords: War and society -- United States; War casualties -- United States; Battle casualties -- United States